2014
DOI: 10.1590/s1516-35982014000700003
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rate in lactating Bos indicus cows subjected to fixed-time artificial insemination and treated with different follicular growth inducers

Abstract: -The objective of this experiment was to evaluate the effects of replacing eCG with FSH or FSH/LH on the diameter of ovulatory follicles (DOF) and the pregnancy rates (PR) of lactating Bos indicus cows subjected to a synchronization of ovulation protocol and fixed-time artificial insemination (FTAI) based on progesterone, estradiol benzoate (EB), PGF2α, and estradiol cypionate (EC). On day 0, primiparous and multiparous Nellore cows (n = 329) at 68 days postpartum were body condition scored (BCS) and received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…Definitely, there is enough evidence in the literature that the inclusion of eCG in an FTAI does not improve the fertility rate in cattle with a good BCS. Binelli et al (2009) mentioned that the eCG effectiveness varies with the BCS and Nogueira et al (2014) observed that the BCS had a positive effect on the probability of pregnancy using eCG in an FTAI. Ferreira et al (2013) indicated that the differences observed in the inclusion of eCG in FTAI might be explained by the corresponding inequalities in BCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitely, there is enough evidence in the literature that the inclusion of eCG in an FTAI does not improve the fertility rate in cattle with a good BCS. Binelli et al (2009) mentioned that the eCG effectiveness varies with the BCS and Nogueira et al (2014) observed that the BCS had a positive effect on the probability of pregnancy using eCG in an FTAI. Ferreira et al (2013) indicated that the differences observed in the inclusion of eCG in FTAI might be explained by the corresponding inequalities in BCS.…”
Section: Discussionmentioning
confidence: 99%
“…Equine Chorionic Gonadotrophin (eCG) has been used in procedures of fixed-time artificial insemination (FTAI) in cattle to try to improve the fertility rate because it produces, among other effects, an increase of follicular growth (Murphy 2012;Núñez-Olivera et al 2014). The application of 400 IU of eCG has shown that it can be a good treatment to increase fertility, especially in beef breeds (Menchaca et al 2013;Nogueira et al 2014); nevertheless, in dairy cattle results have been contradictory (Pulley et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados encontrados en el presente estudio corroboran los datos encontrados por otros autores (15), quienes, trabajando con vacas Nelore, no encontraron diferencias en las tasas de preñez al usar eCG como promotor del crecimiento folicular (46.4%) o FSH (46.3%) comparado al control (41,2%). Por otro lado, algunos autores, comparando el uso de eCG y FSH en vacas Cebú, encontraron tasas de preñez de 55.9 y 51.4% respectivamente, que diferían significativamente de las vacas control, con una tasa de preñez de 38.9% (8).…”
Section: Discussionunclassified
“…Se ha informado que eCG es superior a FSH para estimular las tasas de preñez en vacas; sin embargo, otros autores informaron que no hubo diferencias en el uso de FSH y eCG en vacas sometidas a IATF (7,22). Dichos autores también informaron que el eCG tiene un efecto en la FSH y en la LH, y tiene una vida media más larga, permaneciendo activo en la sangre durante más tiempo, de cinco a siete días después de su administración (15). La FSH utilizada en el presente estudio, por otro lado, contenía el 87% de FSH, y su metabolismo parece ser rápido, ya que, después de la administración intramuscular, la vida media y la desaparición de la FSH se estimaron en 5 y 12 minutos, respectivamente (23,24).…”
Section: Discussionunclassified
“…Alguns autores demonstraram que o sêmen utilizado na IATF tem um grande impacto sobre a TP (CORREA; PACE; ZAVOS, 1997;ANDERSSON et al, 2004;SÁ FILHO et al, 2009;OLIVEIRA et al, 2013OLIVEIRA et al, , 2014NOGUEIRA et al, 2014). A diminuição da fertilidade é uma condição multifatorial, portanto, muito difícil de diagnosticar.…”
Section: Fertilidade Do Tourounclassified